MANAGING TALENTED WORKER IN THE ERA OF NEW PSYCHOLOGICAL CONTRACT - Haryadi, Haryadi; Anggraeni, Ade Irma; Ibrahim, Daing Nasir (Jurnal Aplikasi Manajemen, 2018)
Psychological contract as a strategy based on flexibility has become a new hope in creating competitive advantages with a focus on human resources management is superior. As a concept that powerful, psychological contract be interested in researchers in the field of organizational development in exploring the influence of psychological contract on employee’s work attitude and behavior. But earlier research still gave contradictory results. In the context of managing talented employee, the psychological contract needs to focus on the key factors shaping employee resilience. This research examines the influence of psychological contracts and career resilience on organizational citizenship behavior on employees in the banking sector in Indonesia and Malaysia using structural equation modeling. This research proved the influence of psychological contract on career resilience and the influence or career on organizational citizenship behavior.